Identification and compensation of 11 position-independent geometric errors on five-axis machine tools with a tilting head - Yang, Hui; Huang, Xiaodiao; Ding, Shuang; Yu, Chunjian; Yang, Yameng (International journal of advanced manufacturing technology, 2018)
Position-independent geometric errors (PIGEs), introduced during the assembly process, always affect machining accuracy and shall be identified and compensated periodically. To improve the accuracy of machined parts, this paper proposed an integrated PIGEs identification and compensation method. Three machining patterns were successively performed on a firstly demonstrated artifact. Strategies of single drive of C -axis and effect-reducing in sensitive direction can improve the accuracy of identified results. Corresponding mismatches among a set of machined shallow slots were measured with a coordinate measurement machine (CMM), and mismatches in three coordinate directions were used to decouple the PIGEs based on kinematic error model. To eliminate the effect of PIGEs on machining accuracy, analytical compensation method was presented and verified. Compensated numerical control (NC) codes are calculated by algebraic operation using the analytical expressions which are obtained through only one actual inverse kinematics. Finally, a mismatch machining test had been conducted on a middle-size five-axis machine tool with a rotary table and a tilting head. Verification of the identified values and compensation method was provided. The results showed that the proposed identification and compensation method is effective and applicable.